JURNAL STRATEGI PELATIHAN REYOG SINGO SUMOWICITRO DALAM MENCAPAI PRESTASI PADA FESTIVAL REYOG MINI PONOROGO: WIDI NUR META ZAIN - Zain, Widi Meta (APRON Jurnal Pemikiran Seni Pertunjukan, 2021)
Abstract Reyog State Junior High School 2 Kauman Ponorogo is the Reyog group that often gets achievements in the Ponorogo Mini Reyog Festival. The achievement of the Reyog Junior High School 2 Kauman Ponorogo group was due to Reyog learning with the methods and techniques that were carried out so that research was needed in depth. Reyog Singo Sumowicitro has won various awards from events that were followed, one of which is the Mini Reyog Festival, which in the past 4 years has always been won by the Reyog Singo Sumowicitro group. Apart from the achievements that have been achieved by the Reyog Group, it is a barometer of Reyog-reyog in Ponorogo Regency Middle School and a motorbike for the development of the dance world in Ponorogo Regency. The research revealed that the Strategy of Kauman Ponorogo State Junior High School 2 in Achieving Achievement at the Mini Ponorogo Reyog Festival was by learning methods and learning techniques. The method used is the demonstration method and drill method. While the learning techniques conducted by Kauman Ponorogo 2 Public Middle School are: 1). Hold a Workshop for Jatil and Warok dance. The workshop was attended by several elementary schools in Kauman District. 2). The completion and casting of dancers is in accordance with the character taken because the trainer in choosing dancers is not arbitrary so that the training is truly in accordance with the abilities of educators in their respective fields. In supporting factors, two factors that influence are internal and external factors. In internal factors there are intelligence, physical factors, attitudes, interests, and talents. Then external factors include family factors, school environment and community environment.